Financial Development and Economic Growth in Emerging Markets: The Nigerian Experience - Obamuyi, Tomola Marshal (Indian Journal of Finance, 2012)
The paper provides new evidence on the empirical relationship between financial development and economic growth in Nigeria. Time-series data from 1973 to 2009 were employed to run the econometric analysis of cointegration and Vector Error Correction Model (VECM). The Granger causality test was also adopted to test the direction of causality between financial development and economic growth in the country. The results of the study reveal that there exists a bi-directional causality between economic growth and financial development in the country. The results of this study provide evidence for the government to identify those financial development and growth variables that contribute to the overall economic performance in Nigeria.